Left ventricular outflow tract: intraoperative measurement and changes caused by mitral valve surgery - Rosendal, Christian; Hien, Maximilian; Bruckner, Thomas; Martin, Eike; Szabó, Gábor; Rauch, Helmut (Journal of the American Society of Echocardiography, 2012)
Background: The impact of mitral valve surgery on left ventricular outflow tract (LVOT) dimensions is unclear. Real-time three-dimensional transesophageal echocardiography permits excellent visualization of the LVOT and might improve standard two-dimensional measurements. In this study, LVOT area and shape were assessed before and after mitral valve surgery. Methods: Thirty-five patients undergoing mitral valve repair or replacement were retrospectively included in the study and compared with 15 patients undergoing coronary artery bypass grafting. LVOT area was measured by planimetry. Maximum possible methodologic errors by assuming a circular LVOT and an eccentricity index were calculated. LVOT diameter in a midesophageal long-axis view served to calculate the error for the circular LVOT determined in common intraoperative practice. Results: Common intraoperative two-dimensional measurements underestimated actual LVOT area by 21%. Mitral valve surgery led to a significant reduction of LVOT area by 7%. Although LVOT height remained unchanged, width decreased from 2.72 to 2.53 cm (−7%), resulting in a more circular shape of the LVOT. This effect was more pronounced the smaller the size of the implanted annuloplasty ring or prosthesis. Coronary artery bypass grafting did not affect the LVOT. Left ventricular ejection fraction was significantly correlated with LVOT eccentricity. Impaired ventricular function and higher end-systolic volumes were associated with a rounder shape. Conclusions: The eccentric LVOT shape leads to a distinct underestimation of its area with two-dimensional measurements. LVOT eccentricity is less distinct in patients with low ejection fractions and higher end-systolic volumes. LVOT width is decreased through annuloplasty rings and prostheses, and the smaller the implanted device, the more profound the reduction.